The Relationship Between Disaster Communication Through @bpbddkijakarta Instagram Account on Gen Z's Preparedness Attitudes in Facing Potential Floods in DKI Jakarta - Hotimah, Oot; Sitanggang, Natasya Ananda Rheta (Tecno Scientifica Publishing, 2025)
Floods are a common disaster in Jakarta due to its lowland topography and the presence of 13 major rivers, which are further exacerbated by land subsidence and climate change. Effective disaster communication is essential to enhance public preparedness and mitigate flood impacts. This study examines the relationship between disaster communication through the official Instagram account of BPBD DKI Jakarta (@bpbddkijakarta) and the preparedness attitudes of Gen Z in facing potential floods in Jakarta. The study employed a quantitative approach with a survey method, involving 99 respondents aged 18–25 years who are active Instagram users and have viewed the @bpbddkijakarta reel posted on January 26, 2025. Data were collected using a structured questionnaire with 38 items measuring disaster communication and 21 items measuring preparedness attitudes, analyzed using Pearson’s Product-Moment correlation test. The results show a significant positive relationship between disaster communication and preparedness attitudes (r = 0.769, p < 0.01), with disaster communication explaining 59% of the variance in preparedness attitudes. The findings suggest that improving content quality and fostering two-way interaction on social media could further strengthen disaster preparedness among young people in Jakarta.